Analysis of the Conceptual and Categorical System of Bilingual Education - Yuliya Shyika (Pedagogical Discourse, 2014)
The article deals with the analysis of the scientific-pedagogical literature and concerns the problems of bilingual education and its potential in the organization of secondary education. Advantages and disadvantages of bilingual education that are discussed by different scientists are mentioned in the article. Bilingualism and organization of bilingual education is the object of scientific investigations of pedagogues, psychologists, sociologists etc. It is mentioned in the article that bilingual education forms language and cultural tolerance to different linguistic and cultural groups. Thus, bilingual curriculums provide education in two or more languages and develop language and cultural apprehension.